The Relationship between Market Sentiment Index and Stock Rates of Return: a Panel Data Analysis - Claudia Emiko Yoshinaga; Francisco Henrique Figueiredo de Castro Junior (BAR: Brazilian Administration Review, 2012)
This article analyzes the relationship between market sentiment and future stock rates of return. We used amethodology based on principal component analysis to create a sentiment index for the Brazilian market withdata from 1999 to 2008. The sample consisted of companies listed on BM&FBOVESPA which were groupedinto quintiles, each representing a portfolio, according to the magnitude of the following characteristics: marketvalue, total annualized risk and listing time on BM&FBOVESPA. Next, we calculated the average return of eachportfolio for every quarter. The data for the first and last quintiles were analyzed via two-factor ANOVA, usingsentiment index of the previous period (positive or negative) as the main factor and each characteristic ascontrolling factors. Finally, the sentiment index was included in a panel data pricing model. The results indicatea significant and negative relationship between the market sentiment index and the future rates of return. Thesefindings suggest the existence of a reversion pattern in stock returns, meaning that after a positive sentimentperiod, the impact on subsequent stock returns is negative, and vice-versa.